(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
This article discusses the emotional struggles that gifted and talented students face, which impact their social and academic well-being. The article highlights the importance of creating a supportive environment conducive to the students’ growth, recognizing cultural and socioeconomic factors that may affect the identification and support of gifted students, and providing opportunities for intellectual growth beyond traditional classroom settings. The article suggests practical strategies for fostering peer mentorship and collaboration in the classroom and lists various innovative programs and initiatives that prioritize a strengths-based approach to education for gifted and talented students.